Drama / theatre / performance - Shepherd, Simon; Wallis, Mick (London : Routledge, 2004)
PART ONE: A GENEALOGY Drama and Theatre as university subjects Drama and the literary tradition History, theatre, society The essence of drama Women, theatre and the ethics of the academy Performance, art and the avant garde The rise of Performance Studies Performance studies: some basic concepts Postmodernism and performance Recent mappings of drama-theatre-performance PART TWO: KEYWORDS action aleatory catharsis character, mask, person defamiliarisation and alienation embodiment empathy interculturalism kinaesthetics mimesis performativity presence and representation semiotics and phenomenology
boek